PENDAPATAN DAN FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKSI USAHA TERNAK KAMBING DENGAN LASERPUNKTUR - IDA AYU PUTU PARWATI (Program Studi Agribisnis, Fakultas Pertanian, Universitas Udayana Jalan PB.Sudirman Denpasar, Bali, Indonesia. Telp: (0361) 223544 Email: soca@unud.ac.id, 2007)
ABSTRACT The research aims to know the differences between production cost, revenue and income of goat breeding business by with and whiteout laserpunctur and production factors affecting of goat breeding. The research was carried out in Bongancina village, Busungbiu District, Buleleng Regency from March to June 2003. Primary data was from 60 goats breeders, 36 of them were using laserpunctur technology, and the other 24 were not. To test the differences between both respondent groups, the t-test of statistical procedure was used. The goat breeding income was affected by the number of goat, prices of: germs, selling germs, HMT, Concentrate, goat mother ages, wages and litter size, The Ordinary Least Square (OLS) procedure was applied. The results showed that the level of goat breeder income by using laserpuncture technology was high compared to unusing the technology. Meanwhile, the technology for mass, the concentrate price, and the germ price also affected the goat production. In opposition the litter size affected the goat production. Keywords: Income, Production, Goat, Laserpuncture ABSTRAK Riset bertujuan untuk mengetahui perbedaan biaya produksi, pendapatan dan pendapatan dari bisnis peternakan kambing dengan dan tanpa laserpunctur dan factor-faktor produksi yang mempengaruhi peternakan kambing. Penelitian dilaksanakan di Desa Bongancina, Kecamatan Busungbiu, Kabupaten Buleleng dari Maret sampai Juni 2003. Data primer berasal dari 60 peternak kambing, 36 dari mereka menggunakan teknologi laserpunctur, dan lainnya 24 tidak. Untuk menguji perbedaan antara responden kedua kelompok digunakan statistik t-test. Pendapatan peternakan kambing dipengaruhi oleh jumlah kambing, harga benih, penjualan benih, HMT, konsentrat, umur induk kambing, upah dan ukuran. Hasil menunjukkan bahwa yang tingkat pendapatan peternak kambing dengan penggunaan teknologi laserpuncture adalah lebih tinggi dibandingkan yang tidak menggunakan. Sedangkan teknologi untuk massa pemanasan harga konsentrat, harga benih telah mempengaruhi produksi kambing. Kata kunci: Pendapatan, Produksi, Kambing, Laserpuncture